Getting a Grip on the Grapevine: Extension and Factor Structure of the Motives to Gossip Questionnaire - Dores Cruz, Terence D.; Balliet, Daniel; Sleebos, Ed; Beersma, Bianca; Van Kleef, Gerben A.; Gallucci, Marcello (Frontiers in Psychology, 2019)
Gossip is condemned but also ubiquitous and thought to be essential for groups. This triggers the question of which motives explain gossip behavior. Hitherto, negative influence, social enjoyment, group protection, and information gathering and validation are established as motives to gossip. However, venting emotions – discussed as a potentially important motive – has been overlooked empirically. Furthermore, a lack of consensus about a definition of gossip may have affected previous conclusions about gossip motives. This study (N=460) expands the Motives to Gossip Questionnaire (MGQ; Beersma & Van Kleef, 2012) by including a subscale measuring emotion venting, the desire to share emotionally evocative experiences. To validate the motives to gossip across definitions, we asked participants to report the most recent gossip event they experienced, randomly assigning them to one of three instructions containing different gossip definitions commonly used in the literature: (1) broad instructions (sharing information about third parties who have no knowledge of the exchanged information), (2) narrower instructions (adding the shared information must be evaluative), and (3) instructions using the word gossip. After participants recalled and described a gossip event, they completed the 25-item measure of five motives to gossip: social enjoyment, information gathering and validation, negative influence, group protection, and emotion venting. Confirmatory factor analysis confirmed the five-factor structure. Multi-group confirmatory factor analysis supported full invariance across the three definition conditions. This indicates the Motives to Gossip Questionnaire successfully measures five dimensions argued to motivate gossip and can be applied in research conceptualizing gossip both narrowly and broadly.